Catolicismo e cruzada : revistas católicas e o imaginário anticomunista no Brasil e Argentina : (1960-1967) - Bett , Ianko (2015)
The main objective of this thesis is to analyze the catholic anti-communist discourse that was spread in the journals Catholicism and Crusade in the context of the decade 1960. The Journal Catholicism, published since 1951, was the birthplace of the members who, in 1960, along with Plinio Correa de Oliveira and the Bishops D. Geraldo de Proenca Sigaud and Don Antonio de Castro Mayer founded the "Brazilian Society for the Defense of Tradition, Family and Property" (SBDTFP). For its part, the Journal Crusade, published since the year 1956, consolidated the genesis for the emergence of "Sociedad Argentina de Defensa de la Tradición, Familia y Propiedad" (Argentine TFP), an organization officially established in 1967. Through analysis of the sources in a perspective that included three complementary theoretical levels with each other, namely, the level of representations (Chartier), discourses (Foucault) and imaginary (Baczko), is defended the hypothesis that communism embodied in one of the main "enemies "to be fought by Catholicism and Crusade groups in that context. The thesis presents how was the inclusion of anti-communism in a discursive regularity, which for its heterogeneity, maintained and promoted practices, norms and regulations. These conditions, placed in evidence in moments of disjunction of the Catholic camp (context of the Social Encyclical Mater et Magistra and Pacem in Terris and implementation of Vatican II Council) in times of political crisis (context of the coups of the 1960s) produced the conditions necessary for formatting and operability of the various facets of the imaginary anti-communist in Brazil and Argentina in the 1960s.